On the Turkish transnumeral as an aspect effectuation device - Kutsarova, Sema (East European Journal of Psycholinguistics, 2025)
This paper deals with the phenomenon of the Turkish transnumeral and its interplay with aspect. The transnumeral is a nominal/noun-phrase form interpreted as either singular or plural – i.e., numerically ambivalent and thus different from the standard singular-plural numerical form. Despite the high prevalence of transnumerality in Turkish, its grammatical and semantic description in the literature lags behind the need for a more thorough explanation. The transnumeral form is regarded, on the one hand, as an element which, in its interaction with noun phrases and other sentence components, tends to explicate a certain value in terms of the compositional aspect theory and, on the other hand, as a phenomenon in need of an analysis not paradigmatically vis-à-vis the standard numerical nominal form but in its features and impact at the sentence level. The analyses carried out of the different types of uses of transnumerals in different sentences – as subjects, direct and indirect objects and as certain types of adverbials (instrumental ones)- show that transnumerals cannot be regarded as solely related to the effectuation of imperfectivity, as conjectured by some authors. Transnumerality must necessarily also be interpreted in terms of cognitive processes taking place in the human brain, reflecting the need for language economy and precision. However, the paper shows that, as a general rule, while cognitive processes underlie the effectuation of both number and aspectual values, the system of distribution of the devices responsible for the realization of these values in grammars of different languages does not directly result from cognitive processes. Rather, it is the work of the collective human brain in the construction of language-specific paradigms, such as the singular-plural distinction – as in English, pure transnumerality – as in Chinese, or hybrid systems with simultaneously a singular-plural contrast and transnumerality – as in Turkish.AcknowledgementsFinancial support for this study was provided by the Bulgarian Young Researchers and Postdoctoral Fellows National Program, Part 2, from the Medical University of Plovdiv. I would like to thank the reviewers of my paper for their kind suggestions and the EEJP editorial team for their technical and administrative assistance.